Pengembangan Bahan Ajar Bahasa Arab Berbasis SAVI untuk Meningkatkan Kamahiran Membaca dan Menulis di Perguruan Tinggi/Development of SAVI-Based Arabic Language Teaching Materials to Improve Reading and Writing Skills in Higher Education - Nurul Hidayah; Ana Milhatul Muslihah; Vina Ulil Hidayah; Nurul Hanani (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This study aims to develop Arabic language teaching materials based on the SAVI approach (Somatic, Auditory, Visual, and Intellectual) to enhance university students’ reading (qirā’ah) and writing (kitābah) skills. The challenges faced in Arabic language learning at the higher education level include the lack of instructional materials that comprehensively accommodate students’ diverse learning styles and the continued dominance of conventional teaching methods. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the development show that the SAVI-based teaching materials are effective in increasing students’ motivation, active participation, and their reading and writing skills. Validation by content and media experts indicated that the materials are feasible for use in the learning process. By incorporating elements of movement, sound, visuals, and critical thinking, the SAVI approach has proven to provide a more meaningful and in-depth learning experience for students. This is evidenced by the media expert validation result of 85% (highly feasible), and the content expert validation result of 95% (highly feasible). Product testing showed a feasibility percentage of 97.8% (highly feasible). The next phase, operational testing involving 35 first-semester students of the English Education program, resulted in a score of 84%, indicating a high level of feasibility. Therefore, the SAVI-based Arabic language teaching material product meets the criteria for instructional feasibility.Penelitian ini bertujuan untuk mengembangkan bahan ajar Bahasa Arab berbasis pendekatan SAVI (Somatis, Auditori, Visual, dan Intelektual) guna meningkatkan keterampilan membaca (qirā’ah) dan menulis (kitābah) mahasiswa di perguruan tinggi. Permasalahan yang dihadapi dalam pembelajaran Bahasa Arab di tingkat perguruan tinggi antara lain kurangnya bahan ajar yang mampu mengakomodasi gaya belajar mahasiswa secara menyeluruh dan masih dominannya metode pembelajaran konvensional. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Developmen, Implementation, and Evaluation). Hasil pengembangan menunjukkan bahwa bahan ajar berbasis SAVI ini efektif dalam meningkatkan motivasi, partisipasi aktif, serta keterampilan membaca dan menulis mahasiswa. Validasi ahli materi dan media menunjukkan bahwa bahan ajar tersebut layak digunakan dalam proses pembelajaran. Dengan melibatkan unsur gerak, suara, gambar, dan pemikiran kritis, pendekatan SAVI terbukti memberikan pengalaman belajar yang lebih bermakna dan mendalam bagi mahasiswa. Hal ini ditunjukkan dengan diperoleh dari ahli media adalah 85% (sangat layak), dan hasil dari ahli materi adalah 95% (sangat layak). Hasil uji coba produk menunjukkan persentase persentase 97,8% (sangat layak). Tahap selanjutnya adalah uji coba operasional yang melibatkan 35 mahasiswa semester satu program studi Pendidikan Bahasa Inggris dengan hasil 84%, yang menunjukkan sangat layak. Dengan demikian, produk Bahan ajar bahasa Arab berbasis SAVI memenuhi kriteria kelayakan.